An Analysis on Cohesive Devices of Students’ Recount Paragraphs Writing - Lestari, Feby Tri; Astutik, Indri; Werdiningsih, Indah (Indonesian Journal Publisher, 2023)
Cohesive devices are linguistic elements or techniques used to establish connections and create coherence within a text. They serve to link ideas, sentences, and paragraphs, making the overall discourse more cohesive and facilitating the smooth flow of information. Cohesive devices contribute to the logical organization and understanding of a written or spoken text. By employing cohesive devices effectively, writers can enhance the coherence and cohesion of their texts, allowing readers to follow and understand the information more easily. This study aims to examine how cohesive devices are utilized in recount paragraphs written by students as well as to identify the challenges and underlying reasons for their difficulties in using such devices. The research involved 20 tenth-grade students from MAN 2 Jember and adopted a qualitative analysis research design. The data collection process encompassed documentation, observations, and student interviews. The analysis focused on two aspects of cohesion: lexical cohesion (reiteration and collocation) and grammatical cohesion (reference, substitution, ellipsis, and conjunction). The findings reveal the following: (a) Students employed five types of cohesive devices in their recount paragraph writing, with reference (31.29%) and conjunction (28.75%) being the most frequent, followed by substitution (12.72%), ellipsis (1.78%), as well as reiteration (13.48%) and collocation (11.95%); (b) Students exhibited varying levels of familiarity and competence with different cohesive devices. The study highlights the importance of comprehensive instruction and support to enhance students' proficiency in using cohesive devices. To address the identified challenges, pedagogical interventions are recommended.